The use of GPS analysis to quantify the internal and external match demands of semi-elite level female soccer players during a tournament - Strauss, A.; Sparks, M.; Pienaar, C. (Journal of Sports Science & Medicine, 2019)
The purpose of this study was to make use of global positioning system technology to quantify the internal and external match demands of sub-elite female soccer players. Secondly, the study aims to describe the magnitude of change of these variables within and between matches over the course of a tournament to determine the effect of player fatigue. Thirty sub-elite female soccer players were assessed throughout a local tournament. Differences in match demands within and between matches were assessed using percent difference, effect size and 90% confidence intervals. One-way ANOVA was used to compare differences in the match demands and running intensities among playing positions and Bonferroni corrections were used to determine differences where significant effects of position were observed. A paired sample t-test in conjunction with the Cohen effect size was used to compare changes in match performance. Total distance covered averaged 5917 m. Midfielders covered the greatest absolute and relative total distances, and achieved the highest low-intensity activity and player load per minute of play. Defenders covered significantly (p = 0.05) less relative distance and low-intensity activity per minute of play compared to midfielders. Forwards covered the greatest distance at high-intensity, while the greatest percentage of time at high-intensity heart rate was measured among the defenders. Within match comparisons revealed that player load decreased significantly (p = 0.05) in the second half (ES: 0.4). Relative distance, low-intensity activity and high-intensity activity also decreased in the second half with possibly trivial to likely small changes. Small to large differences in variables were observed throughout the tournament. The biggest magnitude of change was seen with a large decrease (ES: -1.2) in relative distance covered between match 2 and 5. Despite generally small reductions in performance measures, there is evidence that accumulated fatigue throughout a multi-day tournament would affect performance negatively.